Color planning for interiors : an integrated approach to designed spaces - Portillo, Margaret , 1962- (John Wiley & Sons, 2009)
One of the hallmarks of a successful designer is the ability to incorporate color into his or her projects and presentations. Beginning with a description of the multiple facets of color that accomplished designers take into consideration, this book explores color planning through the perspective of creative problem-solving